Kolaborasi Penanganan Stunting - Heni Nurhaeni; Suryati Badrin; Dinarti Dinarti; Made Riasmini; Eska Riyanti (Syntax Corporation Indonesia, 2021)
Stunting is a very bad health condition for a child and his family. Stunting has a major impact on future health status, there are even predictions of economic decline due to stunting conditions. In the midst of a pandemic, the challenges of changing paradigms, reformulating service systems, and modifying innovations are aimed at ensuring prime health services, according to the principles of a health code of ethics. Experimental research and literature study with a focus on stunted children. This research is a collaborative study between nurses, doctors, and health cadres who provide strengthening services to 28 cases of stunting during 2019-2020 in a pandemic. The results showed a significant increase in maternal body weight and knowledge. Collaboration strengthening is carried out in an integrated and significant manner, which is very good for communication, its role, and cooperation. However, the factor of being for Mothers, and children who are always at home during a pandemic, intensive supervision by health cadres is an easy access factor to provide integrated reinforcement.